« Le temps des ténèbres ». La naissance de l’image négative du Moyen Age - Hámori Nagy, Zsuzsanna (Verbum – Analecta Neolatina, 2010)
The Dark Ages is the term popularly applied to describe the period of the Middle Ages. The notion is thought to originate from the sonnets of Petrarch, but it was already used by Saint Bonaventure in the 13th century. Since both authors used the term medium tempus of their tripartition of time to underline the rupture between near and ancient past, its negative connotations became well known to the public and entered historiography through Italian humanism. German humanists, on the other hand, had tried hard to show continuity between the Roman and the Holy Roman Empires in order to support the idea of Translatio imperii Romani a Graecis ad Germanos. However, their efforts had diminished during the new era of reformation which also emphasized the idea of rupture.